Comparative study of macrofungi in different patches of Boshan Community Forest in Kathmandu, Central Nepal - Bhandari, Bhawani; Jha, Sanjay Kumar (Botanica Orientalis: Journal of Plant Science, 2018)
Macrofungi are considered as a group of high-value forest resources worldwide. In this paper, we report species richness and composition of macrofungi in three different forest patches (Schima-Castanopsis, Pinus and Alnus forest) of mid-hill, central Nepal, which were managed under Boshan Community Forest. A Systematic random sampling was applied where 20 rectangular plots of size 10 m x 10 m were laid at 1500 m to 1600 m elevation in each forest type. Species richness and composition of macrofungi were accessed in each forest type. Schima-Castanopsis forest was the richest in terms of macrofungal diversity (70 species), followed by Alnus forest (64) and Pinus forest (56). Polyporaceae was the largest family, followed by Amanitaceae. Agaricales (Rusulla and Amanita) were dominant in Schima-wallichi and Alnus forests, whereas Boletales were dominant in Pine forest. Macrofungal species richness increased with increasing canopy, soil moisture and soil pH. The species richness, however, had weak relationships with litter cover and disturbance. Based on the present study it can be concluded that the study area is rich in macrofungal diversity. Moist soil followed by litter and decaying wood assist the higher diversity of macrofungi. Species diversity is higher in moist and dense canopy forests (like, Schima-Castanopsis and alder) than in open and dry pine forest. Soil moisture, soil pH and tree canopy cover are the most important variables affecting macrofungal diversity. Botanica Orientalis – Journal of Plant Science (2017) 11: 43–48